Efektivitas Samsat Keliling dalam Upaya Meningkatkan Wajib Pajak Masyarakat Kota Medan Perspektif Fiqh Siyasah - Mhd. Fadlan Rawih; Ilhamsyah Pasaribu (LPPM Universitas Ekasakti Padang, 2023)
This research aims to find out how the planning and implementation of mobile samsat increase taxpayers in the people of Medan City from a fiqh siyasah perspective and the factors that influence mobile samsat in an effort to increase taxpayer compliance in the people of Medan City from a fiqh siyasah perspective. The type of research used is qualitative research with a descriptive qualitative approach. The data collection techniques used are observation, interviews and documentation, while the data analysis techniques used are data reduction, data display and data verification. The results of this research show that in terms of management related to the planning and implementation of the mobile Samsat, the principles of fiqh siyasah have been implemented, namely by establishing an institution to manage the regional wealth of Medan City with the principle of objective social benefit which prioritizes the interests of the people rather than individual interests. However, in terms of improving services, we are still not able to contribute optimally, this can be seen from the existence of tax payment brokers who give rise to a negative perspective in society and are not in accordance with Islamic law. The results of this research can provide input to the Mobile Samsat in carrying out the Mobile Samsat Program in an effort to increase taxpayers in the people of Medan City from a fiqh siyasah perspective.